RESULTS OF INTRAVENOUS ALINAMIN AND ALCOHOL EXAMINATION RESULTS IN PATIENTS COMPLAINTS OF SNACTING DISORDERS AT RSMH PALEMBANG - Yoan Levia Magdi; Guntur Bayu Bima Pratama; Erial Bahar (JURNAL KEDOKTERAN DAN KESEHATAN, 2023)
Smell is a chemical substance mixed in the air that humans perceive with their sense of smell. Loss of smell or loss of smell has become very important in recent years. Currently, research on odor is very interesting because it can determine the type of odor, as well as the function of smell. Examination of the intravenous smell test and alcohol smell test is one of the gold standard examinations that can be done to determine the type of smell disorder. To determine the concordance between the results of the intravenous alinamin smell test and the alcohol smell test in patients with olfactory disorders at RSMH Palembang. Observational and analytic research using cross sectional. Data collection was carried out using the medical records of RSUP Dr. Mohammad Hoesin Palembang for the period October 2022 to January 2023. Data were analyzed with IBM SPSS 25. In this study, there were 49 patients with complaints of smell disturbances to the THTBKL department of RSUP Dr. Mohammad Hoesin Palembang. The mean age in the study was 33 years old with the most vulnerable population aged <20 years (26.5%). With the majority of the female sex (57.1%). While the majority of the work is mostly students (26.5%) and complains of gradual disturbance smells (91.8%). Most of the patients who came with complaints of smell disturbances were patients with sinonasal masses (53.1%). The correlation between intravenous alinamin and alcohol smell tests using the Spearman correlation test showed a very strong correlation (r=0.908) and in the conformity test using Cohen's kappa value obtained was 1.000 which means that perfect agreement was reached between the two tests. There is a concordance in the examination results between the alinamin smell test and the alcohol smell test in patients with complaints of smell disorders.